The megacystis-microcolon-intestinal hypoperistalsis syndrome: report of a case and review of the literature - Yiğit, Şule; Barlas, Çiğdem; Yurdakök, Murat; Önderoğlu, Lütfü; Zafer, Yeşim; Saltık, İncinur (The Turkish Journal of Pediatrics, 1996)
The megacystis-microcolon-intestinal hypoperistalsis syndrome is part of a spectrum of intestinal motility disorders and is characterized by abdominal distension, lax abdominal musculature, incomplete intestinal rotation, microcolon, megacystis, bilious vomiting and decreased or absent intestinal peristalsis. In this report a newborn girl with megacystis-microcolon-intestinal hypoperistalsis syndrome is reported.
Keywords: megacystis-microcolon-intestinal hypoperistalsis syndrome; prenatal diagnosis